The demand for long-term mortgage contracts and the role of collateral - Lu Liu (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
Long-term fixed-rate mortgage contracts protect households against interest rate risk, yet most countries have relatively short interest rate fixation lengths. Using administrative data from the UK, the paper finds that the choice of fixation length tracks the life-cycle decline of credit risk in the mortgage market: the loan-to-value (LTV) ratio decreases and collateral coverage improves over the life of the loan due to principal repayment and house price appreciation. High-LTV borrowers, who pay large initial credit spreads, trade off their insurance motive against reducing credit spreads over time using shorter-term contracts. To quantify demand for long-term contracts, I develop a life-cycle model of optimal mortgage fixation choice. With baseline house price growth and interest rate risk, households prefer shorter-term contracts at high LTV levels, and longer-term contracts once LTV is sufficiently low, in line with the data. The mechanism helps explain reduced and heterogeneous demand for long-term mortgage contracts.
Keywords: D15; E43; G21; G22; G5; G52; 330; mortgage choice; house prices; credit risk; interest rate risk; household risk management; household finance